The technological and baking traits of durum wheat - E. N. Shabolkina; P. N. Malchikov; G. N. Myasnikova (Зерновое хозяйство России)
Durum wheat grain is the main raw material for pasta production, but some characteristics of the culture are promising for its use in baking. The flour from durum wheat in its pure form is of little use for bakery products. At the same time the use of 30% of durum wheat flour with its excellent physical and rheological properties of dough gives a positive result in bakery. The study, results of which have been considered in the article was conducted on the experimental plots of the Samara RIA in 2015-2016. The technological traits if grain quality and rheological properties of dough of the 29 varieties of spring durum wheat and their mixtures with spring soft wheat have been studied. The genotypes of durum wheat varieties ‘Bezenchukskaya 209’ and of the lines ‘1389DА-1’, ‘D2098’ and ‘98s-08’ with the best rheological properties of dough have been identified. Good sugar-producing ability of durum wheat and good gas-retaining ability of soft wheat allow baking nutritious and delicious bread with bread volume of 905-980 cm3. But durum wheat flour added to the mixture does not always have the effect of improvement. Not only quality of the durum wheat grain is of great significance but also a selection of the variety which improves and the variety of soft wheat which is being improved.